Changes in labour market transitions in Ireland over the Great Recession: what role for policy? - Adele Bergin; Elish Kelly; Seamus McGuinness (IZA Journal of European Labor Studies, 2015)
This paper assesses the impact the Great Recession had on individuals' transitions to and from unemployment in Ireland. The rate of transition from unemployment to employment declined between 2006 and 2011, while the rate from employment to unemployment increased. The results indicate that young people are much less likely to exit unemployment but, at the same time, have a lower risk of becoming unemployed. Education has become an increasingly important factor in supporting unemployment exits and reducing the risk of unemployment since the recession. The findings are supportive of current policies aimed at facilitating access to higher education for unemployed people, but they raise questions with regard to the adequacy of the Youth Guarantee.
Keywords: I21; J01; J60; J64; J68; 330; Labour market transitions; Great recession; Longitudinal data; Decomposition techniques; Ireland